Mendefinisikan Pengelolaan Keuangan Dalam Keluarga Sakinah: Defining Financial Management Within Sakeenah Family - Hartaty Hadady; Muhsin N. Bailusy; Rheza Pratama; Johan Fahri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
Secularism has been entering every aspect of life, including a micro-level of financial management of a family. This study sheds light on how religious views can be used to minimize the influence of secularism. This study was mainly aimed at demonstrating how sacred goals in Muslim families, through Sakeenah values, can be used as an antidote to secularism practices in managing family finance. Thirteen contextual characteristics of financial management in eight Muslim families were identified using the Grounded Theory method. These characteristics were used to verify main concepts—basic financial management, family structure, Sakeenah elements, and a form of secularism—usury. Using the Grounded Theory method was also the other aim of this study that demonstrated its use to deepen the interrelation between those four main concepts and those characteristics contextually. Several limitations surfaced after the analyses, and this allowed recommendations for future studies.